The Effect of Communication, Decision Making, on Performance by Mediation of Job Satisfaction at the Youth, Sports Office, Culture and Tourism Office Labuhanbatu Regency - Syarifah Nuraini; Zulkifli Musannip Efendi Siregar; Christine Herawati Limbong (Quantitative Economics and Management Studies, 2022)
The purpose of this study was to determine the effect of communication on job satisfaction, to determine the effect of decision making on job satisfaction, to determine the effect of communication on performance, to determine the effect of decision making on performance, to determine the effect of job satisfaction on performance, to determine the effect of communication on performance. performance mediated job satisfaction, to determine the effect of decision making on job satisfaction mediated performance at the Department of Youth and Sports, Culture and Tourism of Labuhanbatu Regency. In this study using quantitative research methods. The population in this study was 70 people, and the sampling technique used was saturated sampling, so that the sample amounted to 70 people. Data collection techniques using documentation, interviews and questionnaires and using a Likert scale instrument for measuring questionnaires. This research uses data analysis method using SmartPLS 3 software which is run on computer media. PLS (partial least square) is a variant-based structural equation analysis (SEM) which can simultaneously test the measurement model as well as test the structural model. The results showed that communication had a positive effect and communication had a positive and significant effect on job satisfaction. Decision making has a positive and significant effect on job satisfaction. Communication has a positive and significant effect on performance. Decision making has no significant effect on performance. Job satisfaction has a negative and significant effect on performance. Communication has a positive and significant effect on job satisfaction mediated by job satisfaction. Decision making has a positive and significant effect on job satisfaction mediated by job satisfaction.